Structural Diversity of a Novel LTR Retrotransposon, RTPOSON, in the Genus Oryza. (January 2016) - Hsu, Yu-Chia; Wang, Chang-Sheng; Lin, Yann-Rong; Wu, Yong-Pei
Retrotransposons with long terminal repeats (LTRs) are the most abundant transposable elements in plant genomes. A novel LTR retrotransposon named RTPOSON primarily occurs in the genus Oryza and in several species of the Poaceae family. RTPOSON has been identified in the Ty1-copia group of retrotransposons because two of its open reading frames encode an uncharacterized protein and UBN2_2 and zinc knuckle, respectively. More than 700 RTPOSONs were identified in Oryza genomes; 127 RTPOSONs with LTRs and gag-pol elements were classified into three subgroups. The subgroup RTPOSON_sub3 had the smallest DNA size and 97% (32/33) of RTPOSON elements from Oryza punctata are classified in this group. The insertion time of these RTPOSONs varied and their proliferation occurred within the last 8 Mya, with two bursting periods within the last 1.5-5.0 Mya. A total of 37 different orthologous insertions of RTPOSONs, with different nested transposable elements and gene fragments, were identified by comparing the genomes of ssp. japonica cv. Nipponbare and ssp. indica cv. 93-11. A part of intact RTPOSON elements was evolved independently after the divergence of indica and japonica. In addition, intact RTPOSONs and homologous fragments were preferentially retained or integrated in genic regions. This novel LTR retrotransposon, RTPOSON, might have an impact on genome evolution, genic innovation, and genetic variation.